Penerapan Rekam Medis Elektronik terhadap Proses Serah Terima Pasien oleh Perawat - Pinandhika Pinandhika; Rr. Tutik Sri Haryati (Journal of Telenursing (JOTING), 2023)
The purpose of this study was to compare the effectiveness of implementing electronic medical records in several countries when nurses hand over patients. The method used in this literature study is a type of systematic review. The author uses the inclusion criteria are journal publications in the 2018-2022 range, with the outcomes analyzed are electronic medical records and patient handovers of 10 journals, and the exclusion criteria are types of literature review research methods. The study results show that the benefits of using electronic medical records during the handover process are that they can improve professional relationships, improve the quality of care, improve patient continuity and communication, reduce negligence and misinformation, and improve patient safety. However, its use still needs to be positively felt by all parties because the role of technology in ensuring the quality of communication and feedback requires continuous evaluation. It has been argued that quality and efficiency can coexist if the organizational culture supports it. Keywords: Communication, Patient Safety, Electronic Medical Records, Nurse Handover